Micrometry of the developing and mature epididymis in goat - Bilaspuri, G S; Kaur, A (The Indian Journal of Animal Sciences, 2012)
The various aspects of micrometry ie. number of tubules/sq.mm. tubular diameter, luminal diameter, thickness of muscular wall, epithelial height and height of stereocilia were recorded in different stages of development (13 days: stage 1. 40 days: stage 2, 4-5 months: stage 3, 1Â½years: stge 4) in the Beetal goat. The significance of the results in relation to age and regions was examined at 5% level. All the micrometric parameters showed age-wise significant variations tor epididymal regions. For all the parameters, except the number of tubules/sq 111, region-wise differences were less marked in stages 1 and 2: the differences increased in stage 3 and became conspicuous at stage 4. The pattern of graphs could differ in various age groups even for the same parameter.